2013
DOI: 10.1021/je400057w
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Berberine Hydrochloride, Ligustrazine Hydrochloride, Colchicine, and Matrine Alkaloids on Macroporous Resins

Abstract: This research aims at identifying suitable resin adsorbents for efficient separation and purification of alkaloids from plant materials. The adsorption properties (equilibrium, kinetics, and column breakthrough) of four alkaloid model compounds (berberine hydrochloride, ligustrazine hydrochloride, colchicine, and matrine) on selected macroporous resins were studied. The adsorption equilibrium capacities and desorption ratios of the four model compounds on nine different macroporous resins were measured and com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…This was a reflection of particle surface 3D morphology and the ability of the adsorbing molecule to access this surface. 34 The 1/ n value is generally applied to estimate whether the adsorption easily takes place. The adsorption can easily take place when the 1/ n value is between 0.1 and 0.5; it is difficult to happen when the 1/ n value is between 0.5 and 1.0, and it is unable to occur when the 1/ n value is great than 1.…”
Section: Results and Discussionmentioning
confidence: 99%
“…This was a reflection of particle surface 3D morphology and the ability of the adsorbing molecule to access this surface. 34 The 1/ n value is generally applied to estimate whether the adsorption easily takes place. The adsorption can easily take place when the 1/ n value is between 0.1 and 0.5; it is difficult to happen when the 1/ n value is between 0.5 and 1.0, and it is unable to occur when the 1/ n value is great than 1.…”
Section: Results and Discussionmentioning
confidence: 99%
“…During the purification process, we chose the macroporous resin as the impurity removal material based on previous studies [18][19][20], and nine resins with different polarity were investigated in the screening test.…”
Section: Discussionmentioning
confidence: 99%
“…1/n greater than 1 rarely occurred. Table 4 shows that the values of 1/n for ECG and EGC on the three resins fall between 0 and 1, which indicated that adsorption easily occurred [34,35].…”
Section: Pseudo-first-order Equationmentioning
confidence: 98%